CORTICOSTEROID THERAPY FOR PATIENTS HOSPITALIZED WITH COMMUNITY-ACQUIRED PNEUMONIA : A SYSTEMATIC REVIEW - Andreria Hatulely, Chrysman (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Pneumonia is an inflammation of the lung parenchyma in the distal terminal bronchioles, which includes the respiratory bronchioles and alveoli. Corticosteroids are routinely used for severe pneumonia symptoms. Numerous studies on adjuvant corticosteroids for community-acquired pneumonia (CAP) have yielded equivocal results. Several systematic reviews and meta-analyses have studied the efficacy of corticosteroids in treating CAP. The aim: This article showed about corticosteroid therapy for patients hospitalized with community-acquired pneumonia (CAP).Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.Result: The PubMed database yielded a total of 423 articles in response to our search query, while the search conducted on SagePub retrieved 491 articles. The search run for the last year of 2013 generated a total of 223 articles from PubMed and 212 articles from SagePub. Ultimately, a cumulative sum of 21 scholarly articles was assembled, with 15 originating from the PubMed database and the other six sourced from SagePub. We have incorporated four studies that satisfied the specified criteria.Conclusion: Administration of steroids as early as possible in patients with severe CAP who are treated to benefit, where they do not experience therapy failure. Slower administration and inadequate doses do not provide any benefit.